IPTEKS BAGI MASYARAKAT PERENCANAAN PAJAK JANGKA PENDEK - Mokoginta, Mia Istiana; Budiarso, Novi Swandari (Jurnal Ipteks Akuntansi Bagi Masyarakat, 2017)
Small business enterprise have a significant contribution for Gross Domestic Product (GDP), however small business enterprise have a lack of manajerial skill, limited funds and marketing. Biji Merah Coffee and Roastery is a small business enteprise at Kota Kotamobagu, Bolaang Mongondow, coffee house that provide coffee, chocholate dan green tea. This coffee house has not implement short profit planning for operating activity. The aims of this research is to increase financial management of small business enterprise coffee house, particularly to estimate future revenues, costs and profit with Cost Volume Profit (CVP) analysis. to plan future levels of operating activity. Method implemented with discourse and trained.